A Development of Deezek.co Ecommerce System - Adib Aqil Ahmad Gisam; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2023)
Dezeek.co is an Instagram user that sells several styles of shoes from various brands via the social media site. Dezeek.co began selling shoes online in 2017 as a student and has continued to do so. Currently they did not have any working website that they can use to sell their products and properly show rating to attract customer trust. The system’s scope is that it will be created by utilizing a website to guarantee that customers and any user can enjoy using the system. The system is developed using object-oriented-approach and using System Development Life Cycle (SDLC)as its model. This is to create functional ecommerce system to help Deezek.co promote it system.HTML and CSS will be user to develop the system for the Deezek.co ecommerce system. Having own website can be beneficial as it can increase business revenue and help to gain customer trust.